Edukasi Gizi Berbasis Aplikasi Android Meningkatkan Pengetahuan Empat Pilar Penatalaksanaan Diabetes Melitus Pada Peserta Prolanis - Fitrah Fitrah; Dita Pulubuhu (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Uncontrolled diabetes could lead to serious complication. Diabetes therapy consists of four pillars where nutrition education is very important in managing the disease. Objective : To analyze the effect of nutrition education (Diabetes’ four pillars management) through android mobile application on the knowledge of Diabetes’ four pillars management in patients with DMT2. Method : A quasi experiment research with a pretest posttest control group design. Twenty-six participants were selected by simple random sampling method. Data were collected based on identity and knowledge which were done by interviewing with questionnaires. Changes on knowledge levels were determined by Mann Whitney test. Result : There were significant changes on knowledges related to diabetes (p=0.034), medical nutrition therapy (p=0.008) and physical exercise (0.014) between intervention and control groups, and there was an increase in pharmacological therapy knowledge but we did not observe any significant differences between intervention and control group (p=0.976). Conclusion : Nutrition education (Diabetes four pillars management) through android mobile application can increase knowledge of diabetes, medical nutrition therapy and physical exercise